Peculiarities of eating behavior and diet of the students of different ages, residing in the villages in Lviv Region - Pasichnyuk, I. P.; Partyka, U. B. (Journal of Education, Health and Sport, 2017)
The article provides results of the research on eating behavior and diet peculiarities of students belonging to various age groups, who studied at secondary schools in the villages and district centers of Lviv Region. It was found that students of different age groups (grades) have certain eating behavior peculiarities, though none of them corresponds to the model of balanced nutrition. In particular, students of 1-4 grades mainly consumed specially cooked food 4-5 times a day at home, did not always eat their entire serve, and often had snacks in between the main meals, eating vegetables/fruits, and bakery. Their behavior during food intake is agitated and unfocused. Eating behavior of secondary school students had the following peculiarities: the majority of students ate 3 times a day and were likely to ignore breakfasts, consumed food cooked for the whole family and did at home, did not always eat all of the offered serve. Instead, at schools they had frequent snacks consisting of vegetables/fruit, bakery, and sweets. With regard to seniors, their eating behavior had its own peculiarities. They were primarily related to active physiologic increase in body growth and weight, the need to spend the whole academic day at school, spend more time on homework, as well as help parents around the house. This research group had 9.7% of persons who had an adequate meal 6 times a day. However, the diet was unbalanced, since most meals where consumed in the afternoon, as well as during evening and night hours. We should also note, that students of 9-11 grades more often than other age groups in the research, ate at school canteens and public catering establishments, ate all of the food offered to them, were calm and attentive during food intake and had the largest number of snacks in between the main meals. What concerns their diet, it did not correspond to the characteristics of the balanced one, when it comes to consuming products required for the growing organism, such as fish, eggs, milk, dairy products, cereals, vegetables, and fruit. Perhaps, this related to the seniors the most. Common drinks among the students of 5-8 and 9-11 grades were colored sparkling water, quass, both home-made and that of industrial production, and 18.1% of seniors regularly consumed non-alcoholic beer. It is interesting, that foods not designated for children – ketchup, sauces, mayonnaise, etc. were among the least noted by juniors, and the most consumed by the group of 5-8 grades. Based on this research, eating behavior of the vast majority of students of various ages is characterized by disorders of the diet and illustrates inadequate approach to understanding the importance of the balanced diet for the subsequent physical and psychological development of the young organism.